2023
DOI: 10.1093/jas/skad231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of liquid diet supplementation while suckling and weaning age on nutritional status, intestinal health, and immunity of piglets pre- and post-weaning

Abstract: New strategies are needed to enhance piglets’ robustness and proper functional development and maturation of piglets’ intestine before weaning, in order to reduce the number of antibiotic treatments of diarrhoeic disorders in newly weaned piglets. It was hypothesised that a liquid nutritional supplement during the suckling period, and/or an increased weaning age, would beneficially impact piglets’ gut health and enhance piglets’ nutritional status before weaning. Further, it was hypothesised that a high intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The use of supplemental liquid milk replacer during lactation is not novel [ 6 , 24 ]; whereas gruel creep feeding is less studied. However, there are some studies that report increased feed intake as well as improved weaning weight when supplemental liquid gruel creep is provided [ 20 , 25 , 26 ]. A study by Heo et al [ 27 ] reported average daily gain ranging from 196 g/d to 221 g/d between D14–D21 in farrowing.…”
Section: Discussionmentioning
confidence: 99%
“…The use of supplemental liquid milk replacer during lactation is not novel [ 6 , 24 ]; whereas gruel creep feeding is less studied. However, there are some studies that report increased feed intake as well as improved weaning weight when supplemental liquid gruel creep is provided [ 20 , 25 , 26 ]. A study by Heo et al [ 27 ] reported average daily gain ranging from 196 g/d to 221 g/d between D14–D21 in farrowing.…”
Section: Discussionmentioning
confidence: 99%